1984
DOI: 10.1021/ic00178a029
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, ESR, electrochemical, and potentiometric titration studies of the imidazolate-bridged dicopper(II) ion in a binucleating macrocycle

Abstract: Physical studies of the imidazolate-bridged dicopper(II) ion coordinated to the ligands l, 4,7,13,16,19-hexaaza-10,22-dioxacyclotetracosane (A) and 1,4,7,13,16,19-hexaazacyclotetracosane (A') were carried out to explore the influence of these binucleating macrocycles on the stability of the Cu2(im)3+ core (imH = imidazole). Temperature-dependent magnetic susceptibility studies of solid [Cu2(im)(imH)2CA](C104)3 and [Cu2(im)CA'](C104)3-H20 revealed antiferromagnetic behavior with J = -27.60 (7) and -29.40 (3) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 1 publication
3
21
0
Order By: Relevance
“…7.0-9.3. When the solution pH is adjusted below 5.6, spectral changes (spectra D-B) were observed, namely the signal at about 3600 G, which is typical signal for imidazolate-bridged Cu(II) complex, decreased and the one at about 3340 G, which is characteristic signal of dinuclear Cu(II) complex, increased indicating that the imidazolate bridge is partially disrupted and probably forms the dinuclear Cu(II) complex 2 (Scheme 2), which are in accordance with the reported results [5]. When the solution pH is proceeded to 3.2 (spectrum A), the signals of free Cu(II) ions appeared, indicating the macrocylic ligand is protonated, and the Cu(II) ions are released.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…7.0-9.3. When the solution pH is adjusted below 5.6, spectral changes (spectra D-B) were observed, namely the signal at about 3600 G, which is typical signal for imidazolate-bridged Cu(II) complex, decreased and the one at about 3340 G, which is characteristic signal of dinuclear Cu(II) complex, increased indicating that the imidazolate bridge is partially disrupted and probably forms the dinuclear Cu(II) complex 2 (Scheme 2), which are in accordance with the reported results [5]. When the solution pH is proceeded to 3.2 (spectrum A), the signals of free Cu(II) ions appeared, indicating the macrocylic ligand is protonated, and the Cu(II) ions are released.…”
supporting
confidence: 90%
“…There is antiferromagnetic interaction with g = 2.08, − 2 J = 66.5 cm − 1 between the two imidazolate-bridged Cu(II) atoms. The complex displays moderate SOD activity with IC 50 of 1.42 μM.Copper(II)-zinc(II) superoxide dismutase (Cu 2 Zn 2 -SOD) is a wellknown metalloenzyme that catalyzes the dismutation of highly toxic superoxide radicals so as to protect cells from the oxidative damage [1][2][3][4][5]. The active site of the enzyme contains an imidazolate-bridged Cu(II)-Zn(II) heterodinuclear metal center, and the reported studies found that the Cu(II) is essential for the SOD activity, while the Zn(II) can be replaced by Cu(II) to give Cu 2 Cu 2 -SOD, which has similar SOD activity as that of Cu 2 Zn 2 -SOD [6,7].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1(a)), similar to that present in reported model compounds [19][20][21][22]. Evidence of the bridge cleavage in 50% aqueous CH 3 CN solution and the key steps of two reactions coupled to the electrochemical processes are presented and their relation with the catalytic activity in the 3,5-di-tertbutylcatechol oxidation shown by the complex is discussed.…”
Section: Introductionsupporting
confidence: 73%